Preparation method and application of recyclable shape memory bio-based carbon fiber epoxy composite material
By preparing eugenol/furan-based epoxy resin composites with carbon fibers, the shortcomings of carbon fiber reinforced resin matrix composites in terms of recycling and shape memory were solved, realizing the recyclability and shape memory capability of bio-based composites, and providing an economical and environmentally friendly recycling method.
Patent Information
- Application Number
- CN202411370269.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-07
AI Technical Summary
Existing carbon fiber reinforced resin matrix composites have shortcomings in terms of recycling and shape memory, making it difficult to achieve efficient recycling and shape deformation.
An epoxy resin-carbon fiber composite material was prepared by combining eugenol/furan-based epoxy resin with carbon fiber, melting and curing it using a solvent-free method, and then recovering the carbon fiber in a specific solvent.
This invention achieves recyclability and shape memory capabilities in carbon fiber composite materials, providing a bio-based composite material that avoids the environmental unfriendliness of traditional petroleum-based materials and offers an economical and environmentally friendly recycling method.
Smart Images

Figure CN119264601A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of polymer materials, and in particular to a preparation method and application of a recyclable novel epoxy carbon fiber composite material. Background Art
[0002] Carbon fiber (CF) is a new type of fiber material with a carbon content of more than 90%, high specific strength, high specific modulus, good electrical conductivity, high temperature resistance and corrosion resistance. Carbon fiber reinforced resin-based composite materials refer to the general term for composite materials with carbon fiber as reinforcement and resin as matrix. They bear the main load in the composite material and make up for the shortcomings of the matrix material such as strength and stiffness. It first appeared as a filament in the electric lamp invented by Edison in the early 19th century. At that time, carbon fiber was obtained by carbonization of cotton, bamboo, etc. Due to its low strength and short life, it was subsequently replaced by tungsten wire. In the early 1950s, with the rapid development of aerospace technology, the requirements for corresponding materials changed from traditional high strength to high strength and light weight. Carbon fiber materials began to gradually receive attention. The Wright Patterson Air Force Base in the United States took the lead in developing viscose-based carbon fibers. In 1959, the UCC company in the United States produced the low modulus viscose-based carbon fiber "Thornel-25", and since then, carbon fiber has begun to be commercialized. In the past six years, carbon fiber and its resin-based composite materials have been widely used in aerospace, military, industry, sports and leisure fields due to their excellent mechanical properties and chemical stability. They are new strategic materials with huge development potential in the future.
[0003] The matrix resin of carbon fiber reinforced resin-based composite materials is divided into thermosetting resins and thermoplastic resins. Commonly used thermosetting resins include epoxy resins, phenolic resins and bismaleimide resins, while thermoplastic resins include polyetheretherketone (PEEK), polyethersulfone (PES) and polypropylene (PP). Thermosetting resins are more widely used because of their better static properties such as strength and stiffness of carbon fiber reinforced composite materials. Summary of the invention
[0004] Purpose of the invention: The technical problem to be solved by the present invention is to provide a preparation method and application of a recyclable shape memory bio-based carbon fiber epoxy composite material in view of the deficiencies in the prior art.
[0005] In order to solve the above technical problems, the present invention discloses a method for preparing an epoxy resin carbon fiber composite material, comprising the following steps: melting an epoxy resin monomer and an aromatic sulfone diamine curing agent by a solvent-free method and then compounding them with carbon fibers, and heating and curing them to obtain an epoxy resin carbon fiber composite material, wherein the epoxy resin monomer is a eugenol / furan-based epoxy resin monomer and has a structure as shown in DEF:
[0006]
[0007] The aromatic sulfone diamine curing agents include but are not limited to 4,4'-diaminodiphenyl sulfone (44DDS) and 3,3'-diaminodiphenyl sulfone (33DDS):
[0008]
[0009] The molar ratio of the epoxy group of the eugenol / furan-based epoxy resin to the amino group of the aromatic sulfone diamine curing agent is 0.8-1.5:1.
[0010] Specifically, the preparation method of the eugenol / furanyl epoxy resin monomer comprises the following steps:
[0011]
[0012] (1) CC coupling: using the coupling of eugenol structure to prepare eugenol / furanyl biphenyl compound a;
[0013] (2) Etherification reaction: 5-chloromethylfurfural is grafted onto the hydroxyl groups at both ends of compound a using a catalyst to obtain compound b;
[0014] (3) Reduction reaction: using a reducing agent to reduce the aldehyde groups at both ends of compound b to hydroxyl groups to obtain compound c;
[0015] (4) Etherification reaction: epichlorohydrin is grafted onto compound c in the presence of a phase transfer catalyst to obtain eugenol / furanyl epoxy resin DEF.
[0016] Wherein, in step (1), the coupled eugenol structure a can be prepared according to the prior art, or can be synthesized in the following manner: eugenol is dissolved in a solvent, commercially available ammonia water is added, and a saturated aqueous solution of potassium ferrocyanide is slowly added dropwise, and then stirred overnight, and the solid obtained by filtering is compound a.
[0017] The solvent is any one or a combination of dichloromethane, ethyl acetate, acetonitrile, acetone, tetrahydrofuran, dioxane and water; in one embodiment, the solvent is a mixture of acetone / water (volume ratio is 2:1); the mass volume ratio of eugenol to ammonia water is 1g:10-15mL; the concentration of ammonia water is ≥25%; the molar ratio of eugenol to potassium ferrocyanide is 1:0.8-1.2; and the reaction is carried out under stirring at a rotation speed of 800-1000rpm.
[0018] In step (2), the molar ratio of compound a to 5-chloromethylfurfural (CMF) is 1:2.2-3.
[0019] The catalyst in step (2) includes but is not limited to sodium iodide, potassium iodide, etc.; the molar ratio of the catalyst to a is 0.08-0.24:1.
[0020] The reaction temperature in step (2) is 50-100° C., preferably 80° C.; the reaction time is 8-24 h, preferably 16 h.
[0021] The post-reaction treatment in step (2) is to dilute the reaction solution with water and an organic solvent, extract it, and purify it by column chromatography; the solvent used includes but is not limited to ethyl acetate, dichloromethane, diethyl ether, etc.
[0022] The reaction solvent in step (3) is a protic solvent, including any one or a combination of methanol, ethanol and water. The concentration of the compound b is 0.05-0.15 g / mL; the reducing agent of the reduction reaction is any one of sodium borohydride, lithium aluminum hydride, aluminum triisopropoxide and hydrogen; the molar ratio of the compound b to the reducing agent is 1:0.25-2.
[0023] The reaction temperature in step (3) is -10°C-10°C, preferably 0°C; the reaction time is 1-2h; after the reaction is completed, an appropriate amount of distilled water is added to quench the reaction and purify to obtain compound c.
[0024] The phase transfer catalyst used in the reaction of step (4) includes, but is not limited to, one of tetrabutylammonium bromide, tetraethylammonium bromide, benzyltriethylammonium chloride or a mixture of several of them.
[0025] In the reaction of step (4), compound c is first dissolved in an organic solvent, and then added to epichlorohydrin, an alkaline solution and a phase transfer catalyst; the organic solvent includes but is not limited to any one or a combination of dichloromethane, ethyl acetate, acetonitrile, acetone, tetrahydrofuran and dioxane, preferably tetrahydrofuran; the alkaline solution is any one or a combination of potassium carbonate solution, sodium carbonate solution, sodium hydroxide solution and potassium hydroxide solution, preferably sodium hydroxide solution.
[0026] In step (4), the molar ratio of the reaction compound c to epichlorohydrin, the base in the alkaline solution and the phase transfer catalyst is 1:10-25:10-25:0.15-0.3.
[0027] The reaction temperature in step (4) is 40-60°C, preferably 50°C; the reaction time is 0.5-8h.
[0028] After the reaction in step (4) is completed, the reaction solution is extracted after dilution with water, dried, filtered, and the filtrate is decompressed to remove the solvent, and the eugenol / furanyl epoxy resin monomer DEF is purified.
[0029] The initial decomposition temperature of the eugenol / furan-based epoxy resin monomer DEF in a nitrogen atmosphere is 254.3°C, the 30% decomposition temperature is 410.7°C, the maximum decomposition temperature is 274.4°C / 445.3°C, and the residual carbon rate at 800°C is 34.5%.
[0030] Meanwhile, the viscosity of the eugenol / furan-based epoxy resin monomer DEF is relatively low, which is 506.3 cP at room temperature (25° C.).
[0031] Based on the above eugenol / furan-based epoxy resin monomer DEF, a thermosetting carbon fiber reinforced resin-based composite material can be prepared by compounding it with carbon fiber.
[0032] The epoxy resin content in the composite material is 30%-80%, preferably 65%-75%; the melting temperature is 100-150°C, preferably 120-130°C; the curing temperature is 160-230°C, preferably 170-210°C, more preferably 170-190°C, and the curing atmosphere is heating curing in a nitrogen atmosphere.
[0033] In one embodiment, the carbon fiber is a carbon fiber woven cloth.
[0034] The epoxy resin carbon fiber composite material obtained by the above preparation method is also within the protection scope of the present invention.
[0035] The carbon fiber composite material prepared by the method of the present invention has a certain degree of processability, shape memory and recyclability. Therefore, the present invention further proposes the use of the above epoxy resin carbon fiber composite material in the preparation of recyclable shape memory materials.
[0036] The present invention also proposes a method for recovering carbon fibers in the carbon fiber composite material, specifically, placing the carbon fiber composite material in N,N-dimethylformamide or acetone solution.
[0037] In this paper, a thermosetting carbon fiber reinforced resin-based composite material was prepared by combining carbon fiber with eugenol / furan-based epoxy resin monomer DEF derived from lignin depolymerization and other pathways. This composite material avoids the environmental unfriendliness and biological toxicity of traditional petroleum-based DGEBA epoxy resin, while showing excellent performance in processability, shape memory and recyclability, providing a new type of bio-based carbon fiber resin-based recyclable composite material.
[0038] Beneficial effects: Compared with the prior art, the present invention has the following advantages:
[0039] (1) The present invention adopts a novel eugenol / furan bio-based epoxy resin, the preparation process of which is highly green, and is a novel bio-based composite epoxy resin. The eugenol and glycosyl 5-hydroxymethylfurfural in the present invention can be obtained by biological preparation method, by conversion or separation from clove oil and biomass such as corn, wheat or straw, and the biological added value of the monomer is very high;
[0040] (2) The epoxy resin substrate provided by the present invention has a certain shape memory capability;
[0041] (3) The carbon fiber epoxy resin composite material provided by the present invention has a high swelling coefficient in acetone and N,N-dimethylformamide, and even decomposes in N,N-dimethylformamide, providing an economical and environmentally friendly method for recycling carbon fiber. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.
[0043] Figure 1 is the IR curve of epoxy monomer DEF;
[0044] Figure 2 It is a shape memory process diagram of eugenol epoxy resin substrate and carbon fiber composite material, where af is the shape memory process of substrate; g is the shape memory process of carbon fiber composite material;
[0045] Figure 3 Schematic diagram of the recovery of DEF / 44DDS-CF composite material by solvent method and SEM image of the recovered carbon fiber, wherein ac is a schematic diagram of the process of recovering DEF / 44DDS carbon fiber; d is a SEM image of carbon fiber precursor; e is a SEM image of the fracture surface of the sample after DEF / 44DDS-CF is dissolved, and f is a SEM image of the surface morphology after DEF / 44DDS-CF is dissolved; g is a scanning SEM image of the carbon fiber obtained by burning the sample with a lighter after resin stripping; h and i are scanning electron microscope images of the carbon fiber after the sample is burned with a flame gun after resin stripping;.
[0046] Figure 4 This is the recovery of the metal mesh of the eugenol / furan epoxy resin composite. The upper picture shows the composite material of DEF / 44DDS and 400 mesh stainless steel wire mesh immersed in DMF for metal recovery; the lower picture shows the composite material of 200 stainless steel wire mesh immersed in DMF for metal recovery. DETAILED DESCRIPTION
[0047] The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0048] Example 1 Preparation of compound a.
[0049] 10.5 g (64.0 mmol) of eugenol was added to a 500 mL flask and dissolved in acetone and water (100 mL / 50 mL) with a volume ratio of 2:1 and stirred evenly. Then 70 mL of ammonia water (25 wt%) was added and stirred for 10 min. Then 21.1 g of potassium ferrocyanide (64.0 mmol, saturated aqueous solution) was added dropwise at a rate of 0.5 mL / min using a syringe pump. After the addition was completed, 70 mL of ammonia water was added and stirred overnight. After the reaction was completed, the solid was filtered out and the filter cake was repeatedly washed with deionized water to obtain product a (10.2 g, yellow solid, yield 96.7%).
[0050]
[0051] 1 H NMR (400MHz, CDCl3) δ6.74 (dd, J=11.3, 1.8Hz, 4H), 6.07-5.93 (m, 2H), 5.16-5.02 (m, 4H), 3.90 (s, 6H), 3.36 (d, J=6.7Hz, 4H).
[0052] Example 2 Preparation of compound b.
[0053] Weigh the prepared compound a (26.1 g, 80 mmol) in a 1000 mL flask and dissolve it in 200 mL acetonitrile. Add potassium carbonate (26.5 g, 192 mmol) and stir for 30 min. Then dissolve CMF (27.6 g, 192 mmol) in 80 mL acetonitrile and add dropwise into the system. At the same time, add sodium iodide (0.96 g, 6.4 mmol). Stir the reaction at 80 ° C and monitor by TLC until the reaction is completed. Dilute the reaction solution with 200 mL deionized water, extract the organic phase with ethyl acetate (200 mL × 3), combine the organic phases, dry them over anhydrous sodium sulfate, filter, remove the solvent under reduced pressure, and purify by column chromatography (petroleum ether / ethyl acetate 4:1) to obtain pure product b (36.9 g, yellow viscous liquid, yield 85.2%)
[0054]
[0055] 1H NMR(400MHz,Chloroform-d)δ9.50(s,2H),7.07(d,J=3.5Hz,2H),6.74(d,J=2.0Hz,2H),6.58(d,J=2.0Hz,2H),6.21(d, J=3.5Hz,2H),5.94(ddt,J=16.8,10.0,6.7Hz,2H),5.19-5.00(m,4H),4.89(s,4H),3.87(s,6H),3.32(d,J=6.7Hz,4H).
[0056] 13 C NMR (101MHz, CDCl3) δ177.80,158.25,152.31,152.21,143.19,137.16,135.99,132.56,122.92,116.09,111.99,111.38,66.61,55.87,39.99.
[0057] HRMS(ESI-TOF)m / z Calcd for C 32 H 30 NaO8[M+Na]+:565.1847, found:565.1833. Example 3 Preparation of compound c.
[0058] Compound b (32.5 g, 60 mmol) was dissolved in 200 mL of methanol, and sodium borohydride (2.3 g, 60 mmol) was added in two portions at 0°C. The reaction was allowed to proceed for about 1 hour. After the reaction was completed as monitored by TLC, an appropriate amount of water was added to quench the reaction, and the organic phase was extracted with ethyl acetate. The organic phase was dried over anhydrous sodium sulfate and filtered, concentrated under reduced pressure, and purified by column chromatography (petroleum ether / ethyl acetate 2:1) to obtain pure product c (26.3 g, yellow viscous liquid, yield 80.2%).
[0059]
[0060] 1 H NMR (400MHz, Chloroform-d) δ6.65(d,J=2.0Hz,2H),6.61(d,J=2.0Hz,2H),6.00(d,J=3.1Hz,2H),5.93(d,J=3. 0Hz,2H),5.91-5.83(m,2H),5.10-4.93(m,4H),4.66(s,4H),4.35(s,4H),3.79(s,6H),3.27(d,J=6.7,Hz,4H).
[0061] 13C NMR (101MHz, CDCl3) δ154.06,152.68,151.36,143.44,137.42,135.39,132 .94,123.47,115.92,111.83,110.23,108.09,66.38,57.41,55.95,40.05.
[0062] HRMS(ESI-TOF)m / z Calcd for C 32 H 34 NaO8[M+Na]+: 569.2162, found: 569.2146. Example 4 Preparation of novel eugenol / furan epoxy resin monomer (DEF).
[0063] Epichlorohydrin (276.2 g, 3000 mmol), tetrabutylammonium bromide (3.7 g, 12 mmol), and aqueous sodium hydroxide solution (48.0 g, 1200 mmol, 50 wt%) were added to a 1000 mL flask, and the mixture was stirred rapidly for 30 min, and the nitrogen atmosphere was replaced. Compound c (32.7 g, 60 mmol) was then dissolved in 100 mL tetrahydrofuran and slowly dripped into the reaction flask, and the reaction was stirred at 50 ° C, and monitored by TLC until the reaction was completed. 200 mL of deionized water was added to dilute the reaction solution, and the organic phase was extracted with ethyl acetate (200 mL × 3). After drying over anhydrous sodium sulfate, the organic phase was filtered and concentrated under reduced pressure, and purified by column chromatography (petroleum ether / ethyl acetate 4:1) to obtain the pure product DEF (36.5 g yellow viscous liquid, yield 92.3%). The monomer has a relatively low viscosity (506.3 cP, 100 rpm, 25 ° C). Fourier infrared test as shown Figure 1 As shown, the characteristic peak of the epoxy group is located at 845 cm -1 、926cm -1 .
[0064] Viscosity test method: test temperature 25°C, sample volume 30mL, rotational viscometer equipment model BROOKFIELDDV-2pro
[0065] Thermogravimetric analysis showed that the initial decomposition temperature in a nitrogen atmosphere was 254.3°C, the 30% decomposition temperature was 410.7°C, the maximum decomposition temperature was 274.4°C / 445.3°C, and the residual carbon rate at 800°C was 34.5%.
[0066] Thermogravimetric testing method: Thermogravimetric analysis was performed at 40-800°C on a TGA-550 system with a nitrogen flow of 20 mL / min and a heating rate of 20°C / min.
[0067]
[0068] 1 H NMR(400MHz,Chloroform-d)δ6.70(d,J=1.9,Hz,2H),6.65(d,J=2.0,Hz,2H),6.14(d,J=3.1Hz,2H),5.97 (d,J=3.1Hz,2H),5.96-5.87(m,2H),5.09-4.99(m,4H),4.72(s,4H),4.42-4.30(m,4H),3.83(s,6H),3.67 -3.62(m,2H),3.34-3.27(m,6H),3.06(ddt,J=5.8,4.2,2.9Hz,2H),2.72 -2.69(m,2H),2.52(dt,J=4.9,2.4Hz,2H).
[0069] 13 C NMR (101MHz, CDCl3) δ152.73,152.09,151.07,143.52,137.41,135.34,132.80,123. 43,115.83,111.97,110.27,110.05,70.49,66.47,65.14,55.97,50.7044.32,40.04.
[0070] HRMS(ESI-TOF)m / z Calcd for C 38 H 42 NaO 10 [M+Na]+:681.2683,found:681.2670.
[0071] Example 5 Preparation of carbon fiber composite material 1.
[0072] Weigh DEF (3mmol, 1.97g) and curing agent 33DDS (1.5mmol, 0.37g) in a reaction bottle, mix thoroughly, slowly heat to 120℃, melt until clear and transparent, then inject into the pre-cut carbon fiber cloth mold for curing reaction, heat and cure in a nitrogen atmosphere, slowly heat to 180℃, and store at 180℃ for 2h. Cut and trim after hot demoulding. Epoxy resin accounts for about 70% of the composite material mass.
[0073] Example 6 Preparation of carbon fiber composite material 2.
[0074] Weigh DEF (3mmol, 1.97g) and curing agent 44DDS (1.5mmol, 0.37g) prepared in Example 4 in a reaction bottle, mix thoroughly, slowly heat to 130°C, melt until clear and transparent, inject into a pre-cut carbon fiber cloth mold for curing reaction, heat and cure in a nitrogen atmosphere, slowly heat to 180°C, and store at 180°C for 2h. Cut and trim after hot demoulding. Epoxy resin accounts for about 70% of the composite material mass.
[0075] Preparation of DEF / 44DDS polymer: DEF (3 mmol, 1.97 g) and curing agent 44DDS (1.5 mmol, 0.37 g) were weighed in a reaction bottle, and after being thoroughly mixed, the temperature was slowly raised to 130°C to melt them until they were clear and transparent, and then injected into a mold for curing reaction. The temperature was slowly raised to 170°C, and stored at 170°C for 2 h, 185°C for 1 h, and 210°C for 1 h, and then naturally cooled to room temperature to obtain a DEF / 44DDS polymer.
[0076] The deformation capacity of DEF / 44DDS polymer samples with a thickness of 4mm was tested. Figure 2 When the polymer is heated to 120℃, the eugenol / furan epoxy resin substrate a is deformed into four different shapes (be, C-type, U-type, S-type, twisted type, in order), and can be fixed in the shape after cooling down. When heated to 120℃ again, it can restore itself to its original shape f; its carbon fiber epoxy resin composite material (as shown in Figure g) can also be fixed after heating, folding and shaping, and then cooled and fixed, and then heated again to restore its shape. This improves the recycling value of the polymer to a certain extent.
[0077] The two carbon fiber composite materials were immersed in N,N-dimethylformamide and observed at room temperature for 72 hours. During the process, it was found that the substrate was gradually peeled off and the carbon fiber was gradually exposed. Taking DEF / 44DDS-CF as an example, Figure 3 (ac) shows the schematic diagram of the solvent recovery process. Figure 3 a is a DEF / 44DDS-CF composite material, Figure 3 b is the comparison of DEF / 44DDS-CF composite material before and after immersion at room temperature. Figure 3 c is the de-resinized carbon fiber and the stripped DEF / 44DDS epoxy resin. After the immersion, the sample was taken out and immersed in N,N-dimethylformamide, and then taken out and dried naturally. The resin detachment degree was calculated by weighing the immersion mass, and the dissociation degree of the composite material was calculated. The carbon fiber composite material before and after de-resinization was characterized by SEM, as shown in Figure 3(di) is shown, d is the SEM image of the carbon fiber precursor; e is the SEM image of the fracture surface of the sample after DEF / 44DDS-CF was dissolved, f is the SEM image of the surface morphology after DEF / 44DDS-CF was dissolved; g is the scanning SEM image of the carbon fiber obtained by burning the sample with a lighter after the resin was stripped; h and i are the scanning electron microscope images of the carbon fiber after the sample was burned with a flame gun after the resin was stripped.
[0078] The dissociation degree calculation formula is: Where m CF is the mass of carbon fiber, m0 is the mass of composite material, m is the mass of recycled carbon fiber, and the calculation results are shown in Table 2.
[0079] Table 1 Dissociation degree of carbon fiber composite materials
[0080]
[0081] The 200-mesh and 400-mesh metal meshes and the DEF / 44DDS composite were immersed in N,N-dimethylformamide and observed at room temperature. During the process, it was found that the substrate was gradually peeled off and the metal network was gradually exposed. Figure 4 The dissociation degrees of the resin in the metal mesh composite material calculated by the above formula are 99.5% and 98.6% respectively.
[0082] The present invention provides a preparation method and application of a recyclable carbon fiber epoxy composite material. There are many methods and ways to implement the technical solution. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the protection scope of the present invention. All components not specified in this embodiment can be implemented by existing technologies.
Claims
1. A method for preparing a recyclable shape memory bio-based carbon fiber epoxy composite material, characterized in that: The method comprises the following steps: melting epoxy resin monomer and aromatic sulfone diamine curing agent by solvent-free method and compounding with carbon fiber, and heating and curing to obtain epoxy resin carbon fiber composite material, wherein the epoxy resin monomer is eugenol / furan epoxy resin monomer and has a structure as shown in DEF:
2. The preparation method according to claim 1, characterized in that: The aromatic sulfone diamine curing agent is 4,4'-diaminodiphenyl sulfone or 3,3'-diaminodiphenyl sulfone, and the molar ratio of the epoxy group of the eugenol / furan epoxy resin to the amino group in the aromatic sulfone diamine curing agent is 0.8-1.5:
1.
3. The preparation method according to claim 1, characterized in that: The preparation method of the eugenol / furanyl epoxy resin monomer comprises the following steps: (1) CC coupling: using the coupling of eugenol structure to prepare eugenol / furanyl biphenyl compound a; (2) Etherification reaction: 5-chloromethylfurfural is grafted onto the hydroxyl groups at both ends of compound a using a catalyst to obtain compound b; (3) Reduction reaction: using a reducing agent to reduce the aldehyde groups at both ends of compound b to hydroxyl groups to obtain compound c; (4) Etherification reaction: epichlorohydrin is grafted onto compound c in the presence of a phase transfer catalyst to obtain eugenol / furanyl epoxy resin DEF.
4. The preparation method according to claim 3, characterized in that: In step (1), eugenol / furanylbiphenyl compound a is prepared by the following steps: dissolving eugenol in a solvent, then adding ammonia water, and slowly adding a saturated aqueous solution of potassium ferrocyanide, stirring overnight, and filtering the obtained solid to obtain compound a.
5. The preparation method according to claim 4, characterized in that: The solvent is any one or a combination of dichloromethane, ethyl acetate, acetonitrile, acetone, tetrahydrofuran, dioxane and water; the mass volume ratio of eugenol to ammonia water is 1g:10-15mL; the concentration of ammonia water is ≥25%; the molar ratio of eugenol to potassium ferrocyanide is 1:0.8-1.2; and the reaction is carried out under stirring at a rotation speed of 800-1000rpm.
6. The preparation method according to claim 3, characterized in that: In step (2), the molar ratio of compound a to 5-chloromethylfurfural is 1:2.2-3; the catalyst is sodium iodide or potassium iodide, and the molar ratio of the amount of the catalyst to a is 0.08-0.24:
1.
7. The preparation method according to claim 3, characterized in that: In step (2), the reaction temperature is 50-100° C.; the reaction time is 8-24 h; after the reaction is completed, the reaction solution is diluted with water and an organic solvent and extracted, and then purified by column chromatography.
8. The preparation method according to claim 3, characterized in that: In step (3), the reaction solvent is a protic solvent, the concentration of compound b is 0.05-0.15 g / mL; the reducing agent is any one of sodium borohydride, lithium aluminum hydride, aluminum triisopropoxide and hydrogen; and the molar ratio of compound b to the reducing agent is 1:0.25-2.
9. The preparation method according to claim 3, characterized in that: In step (3), the reaction temperature is -10°C-10°C; the reaction time is 1-2h; after the reaction is completed, an appropriate amount of distilled water is added to quench the reaction and purify to obtain compound c.
10. The preparation method according to claim 3, characterized in that: In step (4), compound c is first dissolved in an organic solvent and then added to a mixed solution of epichlorohydrin, an alkaline solution and a phase transfer catalyst for reaction, wherein the organic solvent is any one or a combination of dichloromethane, ethyl acetate, acetonitrile, acetone, tetrahydrofuran and dioxane; the alkaline solution is any one or a combination of potassium carbonate solution, sodium carbonate solution, sodium hydroxide solution and potassium hydroxide solution; the phase transfer catalyst is one or a mixture of tetrabutylammonium bromide, tetraethylammonium bromide and benzyltriethylammonium chloride; and the molar ratio of compound c to epichlorohydrin, the base in the alkaline solution and the phase transfer catalyst is 1:10-25:10-25:0.15-0.
3.
11. The preparation method according to claim 3, characterized in that: The reaction temperature is 40-60° C., and the reaction time is 0.5-8 hours. After the reaction is completed, the reaction solution is diluted with water and extracted, dried, filtered, and the filtrate is decompressed and the solvent is removed by rotation to purify the eugenol / furanyl epoxy resin monomer DEF.
12. The preparation method according to claim 1, characterized in that: The melting temperature is 100-150°C.
13. The preparation method according to claim 1, characterized in that: The epoxy resin content in the composite material is 30%-80%, the heating and curing temperature is 160-230° C., and the curing atmosphere is heating and curing in a nitrogen atmosphere.
14. The preparation method according to claim 1, characterized in that: The carbon fiber is carbon fiber woven cloth.
15. The epoxy resin carbon fiber composite material prepared by the preparation method according to any one of claims 1 to 14.
16. Use of the epoxy resin carbon fiber composite material according to claim 15 in the preparation of recyclable shape memory materials.
17. A method for recovering carbon fibers in the epoxy resin carbon fiber composite material according to claim 15, characterized in that: The epoxy resin carbon fiber composite material is placed in N,N-dimethylformamide or acetone solution.
Citation Information
Patent Citations
Bio-based epoxy resin based on paeonol as well as preparation method and application of bio-based epoxy resin
CN115449054A
Magnolol / glycosyl furan double-bio-based epoxy resin monomer as well as preparation method and application thereof
CN116178356A
Biomass recyclable shape memory epoxy resin as well as monomer and preparation method thereof
CN117164532A